SYNTHESIS AND STRUCTURE OF THE NI(II) COMPLEX ON THE BASIS OF THE 4,4-DIMETHYL-3-OXYPENTANAL PARA-METHOXITOBENZOYLHYDRA-ZONE (European Journal of Interdisciplinary Research and Development, 2022)
As a result of the condensation reaction, a new tridentate organic compound was obtained based on the corresponding 4,4-dimethyl-3-hydroxypentanal p-thiobenzoylhydrazone. The planar square NiL · NH3 complex was synthesized by reacting its alcoholic solution with an aqueous ammonia solution of nickel (II) acetate. The composition and structure of the resulting complex were studied by elemental analysis, IR, 1H NMR spectroscopy, and XRD.